Democratic Digital Inequalities: Threat and Opportunity in Online Citizenship From Motivation and Ability. (July 2018) - Beam, Michael A.; Hmielowski, Jay D.; Hutchens, Myiah J.
Internet access provides a number of ways to read, share, and discuss politics. However, the political benefits from technology are most likely afforded to those with greater Internet skill, political interest, and education. This study used nationally representative cross-sectional survey data collected during the 2016 U.S. general election to investigate two online news behaviors. Guided by research on digital inequalities, the opportunities–motivation–ability framework, and communication gaps, we found that Internet skill and political interest, but not education, are related to greater online news reading and sharing. We also found conditional relationships between Internet skill and online news behaviors that were moderated by political interest and education. Skill-based digital inequalities in online news behaviors are exacerbated for those with greater political interest, but the gap is reduced for those with less education. We discuss the threat and opportunity that a digital skill communication gap poses for online citizen engagement.